Game-related statistics discriminating team performances in men's basketball - Dominguez Romero, J.; Gomez Ruano, M. A.; Lorenzo Calvo, A.; Leite, N.; Sampaio, J.; Ortega, E.; Ibanez, S. J. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The purpose of the present study was to identify the basketball game-related statistics that best discriminate performances by level of competition in men`s basketball. Archival data were obtained from International Basketball Federation box-scores for all the games during the 2005 European Championships for Senior ational teams (n= 44), U-20 national teams (n= 56), U-18 national teams (n= 76), and U-16 national teams (n= 68). The game-related statistics gathered included 2- and 3-point field-goals (both successful and unsuccessful), free-throws (both successful and unsuccessful), defensive and offensive rebounds, blocks, assists, fouls, steals and turnovers. As the previous avalaible literature explain, only the close games were selected (N= 122, 1 to 10 points difference). The results from the multivariate analysis showed that the U-16 teams were discriminated from the U-18, U-20 and Senior teams by their lower percentage of assists. On the other hand the U-18 national teams were discriminated from senior and U-20 teams by their lower percentage of fouls, successful free-throws, successful 3-points field-goals and higher percentage of successful and unsuccessful 2-points fieldgoals and offensive rebounds. Coaches can use these results to improve the training process and player recruitment according to level of competition.